Hericium erinaceus, in combination with natural flavonoid/alkaloid and B3/B8 vitamins, can improve inflammatory burden in Inflammatory bowel diseases tissue: an ex vivo study - Gravina, Antonietta Gerarda; Pellegrino, Raffaele; Palladino, Giovanna; Coppola, Annachiara; Brandimarte, Giovanni; Tuccillo, Concetta; Ciardiello, Fortunato; Romano, Marco; Federico, Alessandro (Frontiers in Immunology, 2023)
Hericium erinaceus, berberine, and quercetin are effective in experimental colitis. It is unknown whether they can ameliorate inflammatory bowel diseases in humans. This ex vivo study aimed to evaluate the anti-inflammatory potential of a nutraceutical compound of HBQ-Complex® (H. erinaceus, berberine, and quercetin), biotin, and niacin in inflammatory bowel disease patients. Tissue specimens were obtained either from Normal-Appearing Mucosa (NAM) or from Inflamed Mucosa (IM) in 20 patients with inflammatory bowel disease. mRNA and protein expression of COX-2, IL-10, and TNF-α were determined in NAM and IM biopsy samples (T0). IM samples were then incubated in HBQ-Complex® (with the addition of niacin and biotin), and COX-2, IL-10, and TNF-α tissue levels were evaluated at 120 minutes (T1) and 180 minutes (T2). Incubation with this compound resulted in a progressive decrease in gene and protein COX-2 and TNF-α expression at T1/T2 in the IM. IL-10 showed an opposite trend, with a progressive increase of mRNA and protein expression over the same time window. HBQ-Complex® (with the addition of niacin and biotin) decreased the expression of proinflammatory cytokines at the mRNA and protein levels in IBD tissue. On the contrary, mRNA and protein expression of the anti-inflammatory cytokine IL-10 showed a progressive increase.